Natural gas : Governments and oil companies in the third world - Davidson ann; Hurst chris; Mabro robert (Ibadan : Oxford university press, 1988)
This book examine the third world natural gas and it continued effects on governments and oil companies in development countries. The content further highlights the historical background in defining the clear market for the gas.
include appendix to chapters (266-267)
include index
asm; 05/03/19
Loans
Keywords: Natural gas; Natural gas--Government policy; Developing countries